Inaction in Macro-prudential Supervision: Assessing the EU's Response. Issue 1 (5th March 2019) - Schammo, Pierre
Abstract: In the macro-prudential literature, 'inaction bias' describes the supposed tendency of macro-prudential actors to favour inaction over action when considering the use of macro-prudential tools. While inaction bias is a topic of much interest in macro-prudential policy circles, it has received scant attention from legal scholarship. The aim of this article is to contribute to filling this gap by studying inaction in an EU macro-prudential context and by evaluating the institutional arrangements that were put in place in order to address so-called inaction bias. Several actors at the EU level have a role to play in macro-prudential supervision, especially the European Systemic Risk Board and the European Central Bank (ECB). This paper will assess their capabilities and their capacity to turn these into actions. The role of the ECB will be of particular interest since it was vested with real powers to address possible inaction bias among states participating in the Banking Union. Among other things, I will examine whether the ECB's macro-prudential powers are the cure to the problems that are said to underpin inaction bias at the national level.